Caregiver and child question types during a museum interaction - Thorson, Jill C.; Trumbell, Jill M.; Nesbitt, Kimberly (Frontiers in Psychology, 2024)
Children museums provide an engaging learning environment for families, with exhibits designed to stimulate caregiver-child interactions. Specific types of questions have been shown to support child language learning by scaffolding more elaborative responses. This study analyzed the use of question form types during caregiver-child interactions in a children's museum, aiming to discern their correlation with child language proficiency. We examined and transcribed two exhibit explorations by 43 caregiver-child dyads (3-to 6-year-old children). Our analysis encompasses various syntactic question types (e.g., yes-no, wh-) and measures of child language proficiency, including lexical diversity, morphosyntactic complexity, and overall language ability. Findings reveal disparities in question form usage among caregivers and children, with caregivers predominantly employing closed questions and children balancing closed and open-ended types. Children of caregivers who predominantly posed closed questions exhibited shorter utterances and lower overall language scores. Details on other question forms are presented (sub-types of polar, wh-, alternative, and echo). These findings contribute to our understanding of how question form influences language development and caregiver-child interactions.